The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3892/ol.2016.4965
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of free light chain and heavy/light chain ratios allow diagnosis and monitoring of patients with monoclonal gammopathies: Experience of a single institute, with three exemplar case reports

Abstract: Monoclonal gammopathies are characterized by serum monoclonal component (MC) plus an intact immunoglobulin and a free light chain (FLC), or a combination of both. The measurement of FLC with Freelite® is the standard practice recommended by International Myeloma Working Group guidelines. Recently, Hevylite® heavy/light chains (HLC) assays were introduced to specifically target junctional epitopes between the heavy and light chains of intact immunoglobulins, allowing the independent quantification of the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…However, this MM patient relapsed only secreting monoclonal intact Igs, without showing abnormal serum FLC ratio [26]. This observation suggests that it could be interesting to monitor both HLC and FLC parameters to follow the evolution of clones secreting different types of MPs, as suggested by Gagliardi and colleagues [40]. Additionally, Chae et al observed an alteration of the HLCr in two patients in CR due to decreased uHLC levels.…”
Section: At Follow-upmentioning
confidence: 55%
“…However, this MM patient relapsed only secreting monoclonal intact Igs, without showing abnormal serum FLC ratio [26]. This observation suggests that it could be interesting to monitor both HLC and FLC parameters to follow the evolution of clones secreting different types of MPs, as suggested by Gagliardi and colleagues [40]. Additionally, Chae et al observed an alteration of the HLCr in two patients in CR due to decreased uHLC levels.…”
Section: At Follow-upmentioning
confidence: 55%
“…Ludwig et al demonstrate that rHLC was the first proof of relapse in MM patients relapsing only intact immunoglobulins without any abnormal serum FLC ratios (FLCr) [35]. This evidence encourages the monitoring of both FLC and HLC criteria, analyzing the evolution of clones secreting diverse types of MCs [35,49].…”
Section: The Response Assessment: Rhlc and Dhlcmentioning
confidence: 98%
“…The HLC assays provide an alternative tool to aid in the management of diseases associated with monoclonal intact Ig, including monoclonal gammopathy of undetermined significance (MGUS), smoldering multiple myeloma (SMM) and intact Ig MM 13 . Previous studies found that HLC assays have an important prognostic role and may well assist in monitoring patients, both for benign and AL PCDs 12,14 . In relation to patients with MGUS, a study found that HLC assays provided information about the risk of malignant transformation 15‐17 .…”
Section: Introductionmentioning
confidence: 99%